Match Fatigue Time-Course Assessment Over Four Days: Usefulness of the Hooper Index and Heart Rate Variability in Professional Soccer Players - Rabbani, Alireza; Clemente, Filipe Manuel; Kargarfard, Mehdi; Chamari, Karim (Frontiers in Physiology, 2019)
The aims of the present study were to a) examine recovery time-course and b) analyze the usefulness of the Hooper-Index (wellness index) and resting heart rate variability (HRV) in professional soccer players during an in-season phase. The Hooper-Index and resting HRV were collected on matchday and on the four following days in three consecutive in-season weeks in nine players (25.2±4.3-years). The usefulness of monitoring variables was assessed by a) comparing noise (typical error, TE) to the smallest worthwhile change (SWC) (TE/SWC) and b) comparing match-related changes (i.e., signal) to TE (i.e., signal-to-noise ratio). Between-days standardized differences in the changes of Hooper-Index and HRV were compared to the SWC using magnitude-based inferences. The magnitudes of TE were small and moderate for the Hooper-Index and HRV, respectively. The Hooper-Index showed to be more useful than HRV for monitoring match-induced fatigue as having a lower TE/SWC (3.1 versus 4.4) and a higher signal-to-noise ratio (5.5 versus 1.5). Small-to-very large (range of effect sizes, 0.48; 2.43, confidence limits [0.22; 2.91]) and moderate-to-large (-1.71; -0.61 [-2.44; -0.03]) detrimental changes in Hooper-Index and HRV, respectively, were observed on the days following matchday. While group analyses showed a similar pattern for recovery time-course, more individual players responded similarly when tracked using the Hooper -Index compared to when they were tracked using HRV. An inverse moderate within-individual relationship was observed between changes in the Hooper index and HRV (r=-0.41, [-0.60, 0.18]). The Hooper index is an easy-to-use, no-cost, and non-invasive monitoring tool and seems promising for tracking match-induced fatigue during in the season in professional soccer.